A Co–Fe Prussian blue analogue for efficient Fenton-like catalysis: the effect of high-spin cobalt. Issue 50 (23rd May 2019) - Zhao, Chunxiao; Liu, Biao; Li, Xuning; Zhu, Kaixin; Hu, Ruisheng; Ao, Zhimin; Wang, Junhu
Abstract : We, for the first time, demonstrated using experiments and density functional theory (DFT) calculations that high-spin Co II exhibits excellent Fenton-like activity. Abstract : Herein, we, for the first time, report a high spin Co–Fe Prussian blue analogue (Co–Fe PBA) as a highly efficient Fenton-like catalyst for sulfate radical (SO4 ˙ − ) production. Our experiments and density functional theory (DFT) calculations show that the largely elongated SO4 –OH bond length, strengthened adsorption and facilitated electron transfer for peroxymonosulfate (PMS) activation catalyzed by high-spin (HS) Co II are the main factors contributing to its excellent activity.